On the Sleep of the Computer, or the Performance of Randomness. - You, Mi (Performance Research, 2016)
The article focuses on multimedia art installation "Mirage" by media artist Ralf Baecker and a computer vision program learning algorithm DeepDream developed by American technology company Google. Topics discussed are computational representation of sleeping and dreaming based on the principle of German physician Hermann Ludwig Ferdinand von Helmholtz, using geodynamo data for artificial intelligence and prehension, and understanding relation between virtuality and potentiality using immanence.